BLDC Motor Control for Small Size League Robots - Barros, Valerio A. N. da R.; Maximo, Marcos R. O. A. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper is contextualized in the RoboCup Small Size League, presenting a BLDC motor modeling approach focused on control design for Small Size League robots and proposes two controller architectures: one standard PI controller and one PI controller with the addition of a feedforward gain in order to mitigate the back electromotive force effect, inherent in any electric motor. Furthermore, Monte Carlo simulations were conducted to validate the robustness of both controller architectures. Thus, the contribution of this work is to use formal control theory to develop a robust controller design methodology in order to design a BLDC motor control for Small Size League robots.